Порівняльна характеристика термічних методів переробки пташиного посліду - Скляр, Олександр Григорович; Скляр, Александр Григорьевич; Skliar, Oleksandr; Скляр, Радміла Вікторівна; Скляр, Радмила Викторовна; Skliar, Radmila (ТДАТУ, 2020)
UK: В статті наведено порівняльну характеристику існуючих термічних методів переробки пташиного посліду та осадів стічних вод. Доведено, що термічні способи переробки мають значні переваги перед іншими способами. Наведено, що всі види термохімічної конверсії пташиного посліду дозволяють знизити його об’єм, при цьому отриманий твердий залишок забруднений важкими металами, рухливість яких мінімальна при використанні піролізу. Отримано, що серед термічних методів перевагу слід віддати газифікації і піролізу, так як в результаті цих процесів відбувається конверсія вихідної речовини в газоподібне і рідке паливо, в той час як при спалюванні основним продуктом є теплова енергія. Переробка вихідної вуглеводневої сировини в газ, який має більш широку сферу застосування в порівнянні з рідкою фракцією, представляється найбільш доцільною, в зв'язку з чим газифікація має незаперечну перевагу, що полягає у високому ступені конверсії вихідної сировини в газ. RU: В статье приведена сравнительная характеристика существующих термических методов переработки птичьего помета и осадков сточных вод. Доказано, что термические способы переработки имеют значительные преимущества перед другими способами. Показано, что все виды термохимической конверсии птичьего помета позволяют снизить его объем, при этом полученный твердый остаток загрязнен тяжелыми металлами, подвижность которых минимальна при использовании пиролиза. Получено, что среди термических методов предпочтение следует отдать газификации и пиролизу, так как в результате этих процессов происходит конверсия исходного вещества в газообразное и жидкое топливо, в то время как при сжигании основным продуктом является тепловая энергия. Переработка исходного углеводородного сырья в газ, который имеет более широкую сферу применения по сравнению с жидкой фракцией, представляется наиболее целесообразной, в связи с чем газификация имеет неоспоримое преимущество, заключающееся в высокой степени конверсии исходного сырья в газ. EN: The article provides a comparative characteristic of existing thermal methods for processing poultry manure and sewage sludge. It has been proved that thermal processing methods have significant advantages over other methods: the volume of processed raw materials decreases several times, heavy metals in the composition of the starting material after thermal processing are mainly localized in the solid residue, almost 100% of all organic matter contained in the raw material is processed completely the pathogenic microflora is destroyed. It has been shown that all types of thermochemical conversion of poultry droppings can reduce its volume, while the resulting solid residue is contaminated with heavy metals, the mobility of which is minimal when pyrolysis is used. Also, the properties of products obtained using thermal methods of processing poultry manure are very similar to the properties of products obtained from sewage sludge. As aspecial feature, the low melting point of chicken manure ash can be noted. It was found that, among thermal methods, preference should be given to gasification and pyrolysis, since as a result of these processes, the initial substance is converted into gaseous and liquid fuel, while during combustion, the main product is thermal energy. The processing of the initial hydrocarbon feedstock into gas, which has a wider scope of application in comparison with the liquid fraction, seems to be the most expedient, and therefore gasification has an indisputable advantage, consisting in a high degree of conversion of the feedstock into gas. At the same time, the produced gas has a relatively low calorific value, and the process temperature is such that part of the heavy metals contained in the wastewater sludge evaporates into the resulting gas.
Сравнительная характеристика термических методов переработки птичьего помета
Comparative characteristics of thermal methods for processing bird litter
Keywords: термічні методи; пташиний послід; осадки стічних вод; піроліз; газифікація; спалювання; піролізна рідина; газ; термические методы; птичий помет; осадки сточных вод; пиролиз; сжигание; пиролизная жидкость; thermal methods; bird droppings; sewage sludge; pyrolysis; gasification; combustion; pyrolysis liquid; gas